2009
DOI: 10.1111/j.1439-0264.2009.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Occurrence of Polyovular Follicles in Porcine Ovaries with Particular Reference to Intrafollicular Hormone Concentrations, Quality of Oocytes and their in vitro Fertilization

Abstract: The aim of this study was to identify the occurrence of polyovular follicles in porcine ovaries. We investigated the presence of such follicles in relation to age, and compared the intrafollicular concentrations of steroid hormones between poly- and uniovular follicles. Then we measured the size, viability and the in vitro fertilizing ability of the oocytes from polyovular follicles. Histological examinations documented the occurrence of polyovular follicles in pigs at various stages of follicular growth. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
1
24
1
3
Order By: Relevance
“…Direct correlations between follicular size and quality of the resulting oocytes have previously been described by several authors (Humblot et al, 2005;Mourot et al, 2006;Feng et al, 2007). However, Stankiewicz et al (2009) found several differences in the viability and size of oocytes isolated from the same polyovular follicles, indicating that even the same follicle can contain a highly heterogeneous group of oocytes. On the other hand, Antosik et al (2009) demonstrated that porcine follicular size is highly associated with the expression of genes encoding proteins responsible for the fertilization ability of oocytes.…”
Section: Discussionmentioning
confidence: 81%
“…Direct correlations between follicular size and quality of the resulting oocytes have previously been described by several authors (Humblot et al, 2005;Mourot et al, 2006;Feng et al, 2007). However, Stankiewicz et al (2009) found several differences in the viability and size of oocytes isolated from the same polyovular follicles, indicating that even the same follicle can contain a highly heterogeneous group of oocytes. On the other hand, Antosik et al (2009) demonstrated that porcine follicular size is highly associated with the expression of genes encoding proteins responsible for the fertilization ability of oocytes.…”
Section: Discussionmentioning
confidence: 81%
“…This might be the result of a diversifi ed secretory activity of oocytes from polyooocyte follicles. This suggestion found its confi rmation in the studies conducted by Stankiewicz et al [18], who demonstrated the varied quality of oocytes from polyoocyte follicles. On the other hand, regardless of the number of oocytes and their secretory activity within a follicle, there might be mechanisms responsible for the maintenance of an optimal BMP-15 and GDF-9 concentration to provide for folliculogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…Research into the role of BMP-15 and GDF-9 in the ovarian follicle prove that the mentioned factors are secreted mainly by oocytes. The majority of ovarian follicles contains only one oocyte; however, in some mammal species, there are follicles containing a higher number of oocytes [16][17][18]. The presence of polyoocyte follicles has been recorded, amongst others, in the ovaries of the pig [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations